Mejoramiento CIBER- ADAPTATIVO de los servicios de información médica y promoción de la salud en la región San Martín mediante uso de tecnologías web - Heredia Fernández, Richard (2001)
Our researching design Pre-test and Post-test allowed us in a significant degree evaluate the dependent variable, predicting its behavior, whose projection confirms what is set out in the hypothesis; at the same time the qualitative analysis of the usability results show us a compromise connection and of the expectations from the doctor respect to the web platform that has been developed. For our researching the sample was 23 doctors from a population of 410 doctors attached to the XV Regional Council of the Medical Professional association of Peru. The treatment of the independent variable was transformed in the development of a web platform, being the approach ―The proper Use of Web Technologies", it was permissible due to researching we can reformulate a hypothesis, all under the statistics analysis. The results of the applied survey before, that doctors use the web platform, reveal us their expectations face up to web possibilities, likewise, we were able to observe the lacks and weakness in the theme ofhealth promotion. The results of the applied survey before, after use of the web platforms, show the degree of improving as for o the media and its possibilities. Likewise, the ease as long as the doctors can become familiar with the platforms. Also the results prove that circumstances of the case we take it like an opportunity so that through virtual channels we can expand the doctors possibilities, further away of their clinic action, which typically occur, underlying to that same opportunity space, we establish our researching that is related to all of its beneficiaries (doctors, interested organization in health and unusual users), under the characteristics of a novel service and the promotion and network integration. All of this we summarize it in a multidimensional product (www.sanmartinsaludable.org), with capacity to expand the contents that they are basically related information to healthy lifestyle, health activities, information about the doctors, news, research and the social interaction.